Biosynthesis of delta-aminolevulinic acid by blue-green algae (cyanobacteria). - Kipe-Nolt, J A (1978)
When levulinic acid, a competitive inhibitor of delta-aminolevulinic acid dehydratase, was added to growing cultures of blue-green algae (cyanobacteria), delta-aminolevulinic acid was excreted into the medium and cell growth was inhibited.